Effect of continuous and intermittent exercise training programs on platelet activation of healthy sedentary males - Wan Soriany, Wan Md. Zain (Pusat Pengajian Sains Perubatan, 2013)
The purpose of this study is to investigate the effect of the continuous and intermittent training programs on platelet activation. The hyper-activation of platelet may lead to the development of thrombotic event in cardiovascular disease (CVD). Aerobic exercise is well known to reduce CVD risk and can reduce the platelet activation. There were 24 healthy sedentary males mean aged 21.75±3.73 years old participated in this study and divided into 3 groups which are control group (n=9), continuous group (n=7) and intermittent group (n=8). Platelet activation was measured via detection of the P-selectin and glycoprotein llb-Jlla using jlowcytometry by indirect immunoflourescent. This study observed that, both exercise groups pronounced the better changes. The intermittent type of training showed the decline of the gated percentage of CD62p whereas the continuous group lowering the CD62p and PAC-I activation. As a conclusion, both